New Trends in Aviation and Medical Technology Enabled by Additive Manufacturing - Wegner, Marie; Hartwich, Tobias S.; Heyden, Emil; Schwan, Lukas; Schwenke, Johann; Wortmann, Nadine; Krause, Dieter (Frontiers in Manufacturing Technology, 2022)
In this publication, the potentials of additive manufacturing in the field of sustainability and individualization for aviation and medical technology are presented. Design approaches for each application field as well as examples in the fields are shown. In the field of aviation, structures can be manufactured so that they are load path optimized. This has a great lightweight potential and results in a low resource consumption. The examples contain the design of an aircraft cabin partition using the Direct Energy Deposition process and the optimization of load introduction points directly integrated into the sandwich core. Furthermore, in medical technology, additive manufacturing can be used to produce patient-specific models based on original medical imaging data, which can be used for training of medical treatments, quality assurance or for the validation of new developed medical devices. As examples a stroke simulation model containing a modular aortic model as well as functional stenose models are shown. Furthermore, the use of AM molds to generate a deformable bladder shell and a prostate phantom are described.